Country data on AMR in Brazil in the context of community-acquired respiratory tract infections: links between antibiotic susceptibility, local and international antibiotic prescribing guidelines, access to medicine and clinical outcome. (6th September 2022) - Torumkuney, Didem; Nijhara, Puja; Beltrame, Cristiana Ossaille; Baisch, Elisama Queiroz; Ferreira, Ricardo Macarini
Abstract: Background: Antimicrobial resistance (AMR) is one of the biggest threats to global public health. Selection of resistant bacteria is driven by inappropriate use of antibiotics, amongst other factors. COVID-19 may have exacerbated AMR due to unnecessary antibiotic prescribing. Country-level knowledge is needed to understand options for action. Objectives: To review the situation with respect to AMR in Brazil and initiatives addressing it. Identifying areas where more information is required will provide a call to action to minimize any further rises in AMR within Brazil and to improve patient outcomes. Methods: National initiatives to address AMR, antibiotic use and prescribing in Brazil, and availability of susceptibility data, particularly for the key community-acquired respiratory tract infections (CA-RTI) pathogens Streptococcus pneumoniae and Haemophilus influenzae, were identified. National and international antibiotic prescribing guidelines for CA-RTIs (community-acquired pneumonia, acute otitis media and acute bacterial rhinosinusitis) commonly used locally were also reviewed, along with local antibiotic availability. Conclusions: In Brazil there have been some initiatives addressing AMR such as the National Action Plan for AMR, established in 2018. Antibiotic consumption in Brazil is high but a ban on over-the-counter sales of antibiotics has led to a decrease in consumption. Local antibiotic susceptibility testing needs to be increased and the Survey of Antibiotic Resistance (SOAR) study in Brazil will provide useful data for pathogens causing CA-RTIs. A more standardized inclusive approach in developing local guidelines, using up-to-date surveillance data of isolates from community-acquired infections in Brazil, could make guideline use more locally relevant for clinicians. This would pave the way for a higher level of appropriate antibiotic prescribing and improved adherence. This would, in turn, potentially limit AMR development and improve clinical outcomes for patients.